The cerealisation of the Rhineland: extensification, crop rotation and the medieval ‘agricultural revolution’ in the longue durée - Hamerow, H; Zerl, T; Stroud, E; Bogaard, A (Römisch-Germanische Kommission des Deutschen Archäologischen Instituts, 2022)
This paper presents selected results of a research project designed to generate direct evidence for the spread of low-input cereal farming and crop rotation, key elements of the so-called ‘Medieval agricultural revolution’. This type of farming greatly increased overall crop production, enriching landowners and fuelling population growth. The results presented here situate these developments within the longue durée of farming in the lower Rhine basin, from the Neolithic to the central Middle Ages. They also have important implications for our understanding of agricultural production during the Roman to post-Roman transition.